PAJANAN OKUPASI DARI PASIEN TERINFEKSI HIV DI RSUP SANGLAH DENPASAR - Somia, Agus; Utama IM, Susila; Parwati Merati, Tuti (journal of internal medicine; Vol. 11, No. 3 September 2010, 2012)
Health care personnel who have occupational exposure to blood and some body ! uids or tissues are at risk for HIV infection. Aim of this study to know about characteristics of occupational exposure to HIV who cares in VCT-CST Outpatient Clinic Sanglah Hospital Denpasar. A retrospective descriptive study was done among exposed persons who care in VCT-CST Outpatient Clinic Sanglah Hospital Denpasar during 1 January 2006 ? 31 December 2007. Total 11 cases occupational exposure occurred in health care places, 9 cases occurrence in Sanglah Hospital and 2 cases outside Sanglah Hospital. The profession of exposed persons were doctor (45%), medical student (18.2%) and nurse (18.2%). The type of exposure were percutaneous injury (72.7%). Severity of exposures included, 36.4% KP1 (small volume in short time), 45.5 % KP2 (large volume and/or long time or percutaneous injury with solid needle, or superfesial laceration), and 18.18% KP3 (percutaneous injury with hollow needle, deep injury, visible blood on the device which caused the injury, injury with needle which had been placed in a source patients artery or vein). HIV-positive class I patients (asymptomatic HIV or a low viral load) was 27.3 % and HIV-positive class II (symptomatic HIV or AIDS, acute seroconversion, or high viral load) was 27.3%. about 72% exposed person taken postexposure prophylaxis with combination zidovudine and lamivudine for 4 weeks. Anti HIV status exposed persons at " rst time exposure, 3 month after exposure and 6 month after exposure were negative. We conclude that the most type of exposure were percutaneous with source of exposure each included HIV positive class I dan HIV positive class II. About two third of exposed person taken postexposure prophylaxis with zidovudine and lamivudine combination. Anti HIV status exposed person a " rst time exposure, 3 month after exposure and 6 month after exposure were negative.
Keywords: occupational exposure, HIV infection, VCT-CST Sanglah